Effects of supervised aerobic and strength training in overweight and grade I obese pregnant women on maternal and foetal health markers: the GESTAFIT randomized controlled trial. Issue 1 (December 2016) - Aparicio, Virginia; Ocón, Olga; Padilla-Vinuesa, Carmen; Soriano-Maldonado, Alberto; Romero-Gallardo, Lidia; Borges-Cósic, Milkana; Coll-Risco, Irene; Ruiz-Cabello, Pilar; Acosta-Manzano, Pedro; Estévez-López, Fernando; Álvarez-Gallardo, Inmaculada; Delgado-Fernández, Manuel; et al.
Abstract Background During pregnancy, a sedentary lifestyle may have negative consequences on maternal and foetal health status. The main objective of this project is to assess the effects of an exercise intervention in overweight and grade I obese pregnant on maternal and foetal health markers. Methods/design The present study aims to recruit 60 overweight and grade I obese women interested in participating in an exercise intervention program from the 17th gestational week until delivery. Women will be randomized to either an exercise (three 60-min sessions/week of combined aerobic and strength training and pelvic floor exercises), or usual care (control) group (30 women per group). The primary outcome measures are maternal weight gain, and maternal and neonatal glycaemic profile. Secondary outcome measures are: i) perinatal obstetric records; i) body composition; iii) dietary patterns; iv) physical fitness; v) low-back pain; vi) objectively measured physical activity and sedentary behaviour; vii) haematology and biochemical analyses; viii) oxidative stress; ix) pro- and anti-inflammatory markers; x) bone health biomarkers; xi) sleep quality; xii) mental health, quality of life and positive health. Discussion The findings of this project will help to identify strategies for primary prevention and health promotion based on this exercise-based intervention program among overweight and grade I obese pregnant women. Trial registration NCT02582567 ; Date of registration: 20/10/2015